THE INFLUENCE OF WORKING HOURS AND WORKLOAD ON THE PSYCHOLOGICAL WELL-BEING OF HEALTHCARE WORKERS AT RSU MAHAWIRA PRIMA INDONESIA - Petra Paskani Ndruru; Indah Sari Liza Lubis; Cut Rafyqa Fadhilah (Yayasan Amanah Nur Aman, 2026)
This study aimed to determine the influence of working hours and workload on the psychological well-being of healthcare workes at Mahawira Prima General Hospital, Indonesia. This research employs a quantitative approach with a population of 107 healthcare workers. A sample size of 52 respondents was determined using Slovin's formula. The research instrument was a questionnaire that had been tested for validity and reliability. The data were analyzed using multiple linear regression with t-tests, F-tests, and the coefficient of determination (R²). The results of this study indicated that working hours have a significant influenced on the psychological well-being of healthcare workers (t=2.188; p<0.05). Similarly, workload also significantly affected the psychological well being of healthcare workers (t=3.201; p<0.05). Simultaneously, working hours and workload significantly influenced the psychological well-being of healthcare workers with an F value of 16.147 (p<0.05) and a coefficient of determination of 39.7%. This suggests that 39.7% of the variation in psychological well-being could be explained by working hours and workload, while the remaining 60.3% was influenced by factors outside the scope of this research.